Pengaruh Literasi Keuangan, Sikap Keuangan dan Gaya Hidup Konsumtif Terhadap Perilaku Pengelolaan Keuangan Mahasiswa Pendidikan Ekonomi - Dani Yusuf Bahtiar; Riyanto Efendi; Choirul Hudha; Astrian Kusumawati; Vicky Indarto Setyono (Universitas Pendidikan Ganesha, 2026)
The consumerist behavior often experienced by college students can hinder their ability to manage their personal finances. Factors such as financial knowledge, attitudes toward money, and lifestyle are believed to influence financial management skills. This study aims to analyze the influence of these three factors on the financial management of students in the Economics Education Study Program at the University of Jember. The study used a quantitative approach with a survey method, where data was collected through questionnaires and analyzed using multiple linear regression. The results indicate that financial knowledge and attitudes have a positive influence, while a consumerist lifestyle has a negative impact on financial management. These findings highlight the importance of financial literacy programs and appropriate financial attitude training to reduce consumerist behavior.